Freelancer – “The spirit of the globally desirable stateless citizen” - Živković, Predrag (Sociološki pregled, 2022)
The review of the work “Working from Home – Economic, Legal and Socio-Psychological Aspects of Working from Home” lists the features of the culture and history of work that may be considered a map of information capitalism, although work from home can be traced back to not so modern or recent epochs. However, what is in the focus of this “research reformation” of the team of authors are definitely new models of (self)employment that, as it can be clearly seen in the authors’ statements, arise or have arisen as independent paradigms in relation to the COVID-19 pandemic. On the other hand, the pandemic encouraged the conduct of a number of compatible studies whose socio-psychological comparisons are used by the authors as a basis to justify their originality. The monograph clearly emphasizes the demarcation claims of working from home, as well as other “horizon of information existence”, or a new entrepreneurial culture. Therefore, apart from the ever more present work culture that is reflected in working from home in informatic capitalism, our task is also to show the results of indicating the possibility of legal, economic and socio-psychological development of freelancers as an entrepreneurial layer in the Serbian society.
Keywords: working from home; self-employment; freelancers; neoliberalism; information capitalism